Group portrait in Government House, film crew, with Prime Minister Pierre Elliot Trudeau, BC Premier Bill Bennett, and Karl Spreitz, with unidentified dignitaries (2021)
Group photograph inside Government House, featuring film crew, Prime Minister Pierre Trudeau, Karl Spreitz, and others.